Isolation of beta-sitosterol and evaluation of antioxidant Activity of Iraqi Campsis grandiflora flowers. - Hassoon, Sara Saad; Saleh Abbas , Ibrahim; Abdul Razzaq Mshimesh, Bahir (Iraqi Journal of Pharmaceutical Sciences, 2022)
Campsis grandiflora (Bignoniaceae) is a fast growing deciduous climber, the dried flowers have been used as a carminative, blood tonic, and febrifuge in Chinese traditional medicine. This plant has an anti-inflammatory, anti-oxidant, anti-depressant, and anti-bacterial effect; with a beneficial role in stagnant blood and endometriosis conditions. In this study, the detection of beta-sitosterol in the hexane extract of Iraqi C.grandiflora flowers was performed using thin layer chromatography (TLC) and high performance liquid chromatography(HPLC); while the isolation done by preparative layer chromatography then structure elucidation of isolated compound was done by FTIR and 1HNMR. Furthermore, assessment of the anti-oxidant activity of the ethyl acetate extract of Iraqi C.grandiflora flowers using three different methods and total flavonoid content, then measuring the pearson’s correlation coefficient between these methods. The results showed that the hexane extract of Iraqi C.grandiflora flowers contain beta-sitosterol compound and the ethyl acetate extract of this plant possesses an excellent anti-oxidant effect using the single-electron transfer (SET) pathway in scavenging the free radicals, and this activity attributed to the potent antioxidant i.e. polyphenols.